High-Density Lipoprotein Cholesterol and the Risk of First Ischemic Stroke in a Chinese Hypertensive Population - Zhang Y (Dove Medical Press, 2021)
Yue Zhang,1 Jingyi Li,2 Chengzhang Liu,3 Hongxiang Yu,1 Chen Chen,1 Chonglei Bi,4 Chongqian Fang,4 Hai Ma,5 Aimin Li,6 Qing Dong,7 Lishun Liu,8 Binyan Wang,3 Xiao Huang,9 Xiaoshu Cheng,9 Pierre Zalloua,10 Xiping Xu,11 Yong Huo,12 Gang Li1 1Department of Neurology, East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 2State Key Laboratory of Natural Medicines, Research Center of Biostatistics and Computational Pharmacy, China Pharmaceutical University, Nanjing, People’s Republic of China; 3Shenzhen Evergreen Medical Institute, Guangzhou, People’s Republic of China; 4People’s Hospital of Rongcheng, Rongcheng, Shandong, People’s Republic of China; 5Health and Family Planning Commission, Rongcheng, Shandong, People’s Republic of China; 6Department of Neurosurgery, Lianyungang Clinical College of Nanjing Medical University, Lianyungang, People’s Republic of China; 7Lianyungang Health Committee, Lianyungang, Jiangsu, People’s Republic of China; 8Beijing Advanced Innovation Center for Food Nutrition and Human Health, College of Food Science and Nutritional Engineering, China Agricultural University, Beijing, People’s Republic of China; 9Department of Cardiovascular Medicine, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 10School of Medicine, Lebanese American University, Beirut, Lebanon; 11Division of Nephrology, Nanfang Hospital, Southern Medical University; National Clinical Research Center for Kidney Disease; State Key Laboratory of Organ Failure Research; Guangdong Provincial Institute of Nephrology, Guangzhou, People’s Republic of China; 12Department of Cardiology, Peking University First Hospital, Beijing, People’s Republic of ChinaCorrespondence: Gang Li 1800 Yuntai Road, Shanghai, 200123, People’s Republic of ChinaTel +86-21-38804518-22107Fax +86-21-58798999Email ligang@tongji.edu.cnBackground and Purpose: Elevated high-density lipoprotein cholesterol (HDL-C) levels have displayed protection against cardiovascular disease. However, the association between specific lipoprotein classes and first ischemic stroke (IS) has not been well defined, particularly in higher-risk hypertensive populations. Our study evaluated the associations of HDL-C with first IS in a Chinese hypertensive population.Methods: The study population was obtained from a community-based cohort study of hypertension in Lianyungang and Rongcheng, China. A nested case-control design was used that included 2463 identified first IS cases and 2463 controls matched by age ± 1 year, sex, and region.Results: After adjusting for potential confounders, HDL-C was inversely associated with first IS (adjusted odds ratio [aOR]: 0.91; 95% confidence interval [CI]: 0.85– 0.98). HDL-C levels of at least 65.4 mg/dL displayed a significant protective effect for first IS (aOR: 0.82; 95% CI: 0.69– 0.98). Conversely, adverse effects of first IS were observed for low-density lipoprotein cholesterol (LDL-C) levels ≥ 138.1 mg/dL (aOR: 1.20; 95% CI: 1.02– 1.42) and triglyceride (TG) levels ≥ 140.8 mg/dL (aOR: 1.27; 95% CI: 1.09– 1.49). The risk associations of LDL-C and TG with first IS were attenuated in the presence of high HDL-C (≥ 53.0 mg/dL); an increased risk of first IS was only found in the presence of low HDL-C (< 53.0 mg/dL) when LDL-C (aOR: 1.66; 95% CI: 1.19– 2.31) and TG (aOR: 1.47; 95% CI: 1.17– 1.84) were combined with HDL-C for analysis.Conclusion: In this community-based Chinese hypertensive population, higher HDL-C was a significant protective factor of first IS. These data add to the evidence describing the relationship between lipids and IS and suggest that HDL-C maybe is a marker of IS risk in Chinses hypertensive population.Keywords: high-density lipoprotein cholesterol, lipids, ischemic stroke, epidemiology